42 a case of hysterical deafness and its management - Greval S; Bhagat Singh (Journal of All India Institute of Speech and Hearing, 1977)
Psychogenic deafness (Fowler, 1959), or nonorganic ('functional') hearing loss (Chaikhn and Ventry, 1963), or pseudohypoacusis (Goldstein, 1966) can be broadly divided into hysterical, or conversion, deafness and malingering. The former is marked by the fact that the patient believes that he or she has a genuine hearing loss, or that the moderate loss of hearing he or she has is a really serious one (functional 'overlay' on organic deafness). The hysterical patient is not trying to 'fool' anyone and is perfectly willing to cooperate in a test situation.